Represents Fantasi Seksual dalam Film Dear David dengan Analisis Naratif Tzevetan Todorov - Arief Rachman Susilo; Dewi Sri Andika Rusmana; Novan Andrianto (Jurnal Nomosleca, 2024)
The aim of this research is to describe the representation of sexual meaning in the film "Dear David". The research method uses a qualitative method with Tzevetan Todorov's narrative analysis structure which looks at films from the beginning, middle and end of the plot, and uses Stuart Hall's representational communication theory. The results of this research show that the film "Dear David" can represent adolescent sexual fantasies, in the form of a representation of women's lack of freedom in expression, a woman's resistance and leadership in terms of sexuality, a woman's satisfaction in using sexual tools and the beginning of a new love story. It is hoped that this research can provide additional information regarding adolescent sexual fantasies represented in the film "Dear David" and that further research can further develop various aspects and other analytical methods.